Production and decay of anticharmed pentaquark state with quark content $$\bar{c}sudd$$ c ¯ s u d d - Shi-Dong Liu; Xiao-Yun Wang; Xiao-Hai Liu; Gang Li (European Physical Journal C: Particles and Fields)
Abstract We use an effective Lagrangian approach to investigate the production of the anticharmed pentaquark state $$P_{\bar{c}s}^{(*)-}$$ P c ¯ s ( ∗ ) - with the minimal quark content $$\bar{c}sudd$$ c ¯ s u d d in the $$Λ _b^0$$ Λ b 0 decay. In our calculation, the $$P_{\bar{c}s}^{(*)-}$$ P c ¯ s ( ∗ ) - is considered as the molecule state of the $$nD_{s0(s1)}^{-}$$ n D s 0 ( s 1 ) - in an S wave, and its production and decay occur via triangle loops at the hadron level. With the moderate model parameters, the computed results suggest that the branching fractions of $$Λ _b^0→ P_{\bar{c}s}^{(*)-} D^+ $$ Λ b 0 → P c ¯ s ( ∗ ) - D + can reach approximately $$10^{-4}$$ 10 - 4 . The possible decay modes $$ P_{\bar{c}s}^{(*)-} → Λ D^{(*)-}$$ P c ¯ s ( ∗ ) - → Λ D ( ∗ ) - and $$ P_{\bar{c}s}^{(*)-} → Σ D^{(*)-}$$ P c ¯ s ( ∗ ) - → Σ D ( ∗ ) - are also investigated. It is hoped that these predictions could be helpful in searching for the anticharmed-strange pentaquark candidates in future LHCb experiments.